Avaliação do potencial do uso da sílica de casca de arroz obtida através da queima controlada como substituição parcial ao cimento Portland na produção de concretos autoadensáveis - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This study aims to evaluate the potential use of rice husk silica (RHS), obtained under controlled burning conditions, such as partial replacement material to the Portland Cement (PC) in the production of self-compacting concrete (SCC). The RHS employed in this study was produced under controlled conditions in a fluidized bed combustion system, resulting in highly amorphous silica and of good quality. We evaluated the results of the rheological behavior of SCC in the fresh state and strength in the hardened state of a reference concrete without the use of RHS and five concrete made from partial substitution 5%, 10%, 15%, 20% and 25% in RHS relative to the amount of concrete mass. In all traces were used 15% of Fly Ash (FA) is added to the mass of the binder material to assist in reducing friction between particles of the aggregates with cement. The trace of the reference concrete was obtained using the experimental procedure proposed by Gomes method. This trait was also analyzed by the method of packaging compressible and based on this method are defined partial strokes with other PC for RHS substitutions. After obtaining the characteristics of the materials and dosages of SCCs, these were featured in the fresh according to the Brazilian standard NBR 15823/2010, as follows: Spreading tests on cone Abrans and "J-ring", pour in "V-Funnel" and passing ability in the "L-box" and "U-box". The results shows that concrete made with RHS have good flow capacity. In the hardened state the mechanical resistances were checked axial compression and tension by diametrical compression of SCCs at the ages of 7, 28, 56 and 91 days. The test results indicate that it is possible to replace PC with RHS without prejudice to the characteristics of SCCs and still get technical and economic gains. The best concrete, taking into account all the points studied, was the one with replacement of 15% of PC for RHS.
Keywords: Engenharia; Tecnologia dos materiais; Concreto autoadensável; Engineering; Materials technology; Self-compacting concrete